Ways to Increase the Effectiveness of Interfaculty Students' Physical Activity - Usmonov Mansur Qurbonmurotovich (Scientific Trends, 2025)
The article considers the problem of increasing the physical activity of interfaculty students in higher education institutions and its relevance. The impact of physical activity on students' health, success in the educational process and general development is analyzed. The study proposes new pedagogical strategies and innovative methods aimed at increasing the physical activity of students. In particular, recommendations are made in such areas as organizing sports events taking into account the interests and needs of students, holding interfaculty sports competitions, improving physical education classes, and encouraging students to engage in physical education on their own.
Keywords: Physical activity, students, interfaculty activities, sports, healthy lifestyle, pedagogical strategies, innovative methods.